Comparison of methods to monitor dogs with hypercortisolism treated with trilostane. (21st October 2021) - Golinelli, Stefania; de Marco, Viviani; Leal, Rodolfo Oliveira; Barbarossa, Andrea; Aniballi, Camilla; Maietti, Elisa; Tardo, Antonio Maria; Galac, Sara; Fracassi, Federico
Abstract: Background: The use of adrenocorticotropic hormone stimulation test as method to monitor efficacy of trilostane treatment of hypercortisolism (HC) in dogs has been questioned. Objectives: To evaluate and compare 12 methods with which to monitor efficacy of trilostane treatment in dogs with HC. Animals: Forty‐five client‐owned dogs with HC treated with trilostane q12h. Methods: Prospective cross‐sectional observational study. The dogs were categorized as well‐controlled, undercontrolled, and unwell through a clinical score obtained from an owner questionnaire. The ability to correctly identify trilostane‐treatment control of dogs with HC with the following variables was evaluated: before trilostane serum cortisol (prepill), before‐ACTH serum cortisol, post‐ACTH serum cortisol, plasma endogenous ACTH concentrations, prepill/eACTH ratio, serum haptoglobin (Hp) concentration, serum alanine aminotransferase (ALT), gamma‐glutamyl transferase (γGT) and alkaline phosphatase activity, urine specific gravity, and urinary cortisol : creatinine ratio. Results: Ninety‐four re‐evaluations of 44 dogs were included; 5 re‐evaluations of 5 unwell dogs were excluded. Haptoglobin was significantly associated with the clinical score ( P  < .001) and in the receiver operating characteristic analysis, Hp cutoff of 151 mg/dL correctly identified 90.0% of well‐controlled dogs (specificity) and 65.6% of undercontrolled dogs (sensitivity). Alanine aminotransferase ( P  = .01) and γGT ( P  = .009) were significantly higher in undercontrolled dogs. Cutoff of ALT and γGT greater than or equal to 86 U/L and 5.8 U/L, respectively, were significantly associated with poor control of HC by trilostane. Conclusions and Clinical Importance: Of all the 12 variables, Hp, and to a lesser degree ALT and γGT, could be considered additional tools to the clinical picture to identify well‐controlled and undercontrolled trilostane‐treated dogs.